Penguatan Nilai Karakter dalam Cerita Anak “Little Abid Balita Cerdas & Saleh” Karya Tim Cordoba Kids - Muharrina Harahap (Universitas Mulawarman, 2022)
This article examines the character values ​​contained in the children's story series